Understanding the relationship between environment, agriculture and health: An interdisciplinary challenge - Jeff Waage (Indonesian Journal of Applied Environmental Studies, 2022)
In an editorial last year, Prof. Kathryn Monk explained the importance to environmental research of an interdisciplinary approach. She has asked me to share with readers some further, personal thoughts on this topic. I am an ecologist by training, but I spent much of my career managing agricultural research programmes in tropical regions. For the last ten years, I have held a position in a school of public health. This varied disciplinary experience has given me the opportunity to explore and understand interactions between environment, agriculture and human health. It is helpful to think of environment, agriculture, and health as points in a triangle, each having specific interactions with an adjacent sector, but also being influenced by more complex, three-way interactions. For environmental scientists, the interactions with agriculture are probably the most familiar. Extensive planting of crops like rice and oil palm has dramatic effects on biological diversity, water systems and their function, and soils. The importance of healthy environments to agriculture is repeatedly demonstrated. Thirty years ago, I had the opportunity to review the Indonesian national programme on integrated pest management in rice. Use of pesticides on rice was, paradoxically, causing severe outbreaks of pests like brown planthopper. The environmental processes behind this were actually quite complex. Soon after flooding, aquatic arthropods colonizing rice paddies provided a food source for generalist predators that moved in and built levels capable of suppressing subsequent pest invasion. Pesticides killed off this general predator community, while the pests, which lay their eggs inside plants, were less affected and their populations exploded in this predator-free environment (Settle et al. 1996).  Integrated Pest Management (IPM) on rice, pioneered in countries like Indonesia, was for many years a leading example of the value of integrating environmental and agricultural research.Environmental scientists will be less familiar, perhaps, with the interactions between agriculture and health, so here is a short introduction. Agricultural systems have two impacts on health, which for historical reasons have been treated as separate disciplines in the health sector. They produce food that contributes to nutrition, which is usually, but not always, a health benefit, and they produce distinct health risks, including diseases associated with food and food production, and toxins associated with agriculture, such as the pesticide just mentioned.